The Contribution of Self-Control towards Student Smartphone Addiction - Rizki Adiyatma; Mudjiran Mudjiran; Afdal Afdal (Indonesian Counselor Association (IKI), 2020)
The presence of smartphones has caused major changes in human life, including among students. This causes the problem of smartphone addiction in students which causes their daily life to be disrupted. This study aims to reveal the contribution of self-control towards student smartphone addiction. This study was descriptive quantitative, and the data were analyzed by using a simple linear regression. The population in this study was 33480 students of undergraduate program at Universitas Negeri Padang in 2015-2019 academic year. The sample of this study was 400 students taken by using the Proportional Random Sampling technique. The research instrument used was the self-control and smartphone addiction scale with a Likert scale model. The research findings revealed that self-control gives an effective contribution towards the student smartphone addiction at Univeristas Negeri Padang as many as 30.1%.